Modelling thermal dependent phenomena of MOX fuel with focus on thermal conductivity - Ahmed, Aly (My University, 2015)
Among the parameters that govern the myriad of processes that occur during irradiation of fuel rods, the fuel temperature is by far the most important one. The correct prediction of the fuel temperature profile is therefore the basis for the simulation of integral fuel rods by means of fuel performance codes. It is therefore of critical importance to any computer code used for simulation of integral fuel rod behavior to be able to predict the thermal conductivity of the fuel correctly since it directly affects the temperature. The present activity is conducted in the framework of the PELGRIMM EC Project and deals with the assessment of MOX fuel conductivity correlations used in the TRANSURANUS code and comparing them to open literature correlations and experimental data then verifying the code against selected integral fuel rod experiments done for both thermal and fast reactors. In order to assess the thermal conductivity correlations of MOX fuel, other phenomena that would affect the prediction of temperature have been investigated as well in order to capture the integral behavior of MOX for thermal and fast reactors. This step helped in assessing the ability of thermal conductivity correlations to predict fuel temperature while excluding the effects of other phenomena meanwhile giving a general information about the ability of different models to predict the phenomenon they predict. It was shown during this work that TRANSURANUS is able to predict temperature, hence the thermal conductivity of thermal reactor MOX with high accuracy. On the other hand, the work revealed a potential field of improvement to predict the thermal conductivity of FR grade MOX, especially if not of stoichiometric grade and if in fresh conditions. However, the code seems to be on the conservative side when modeling FR MOX. A first step in this improvement was taken in this work and targeted the modification of the high temperature thermal conductivity term in order to be able to obtain a better, less conservative prediction of the melting of FR fuel rods early in life in the reactor core.
Keywords: Energi; Beräkningsfysik; Teknisk fysik; Energy; Computational physics; Engineering physics